2016
DOI: 10.1111/tid.12530
|View full text |Cite
|
Sign up to set email alerts
|

In kidney transplant recipients with BK polyomavirus infection, early BK nephropathy, microvascular inflammation, and serum creatinine are risk factors for graft loss

Abstract: These observations suggest that, in patients with BK infection, early BKVN, Scr >2, and MVI are predictors of poor outcomes. Further studies are needed to determine effective treatment strategies for BKVN, with or without AMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…Study of the histologic evolution of BK nephropathy has recently shown the link between BK nephropathy and antibody‐mediated rejection, but in both studies were limited by their lack of standardized de novo DSA screening . Previous work has shown that features of antibody‐mediated rejection (glomerulitis and peritubular capillaritis) in the setting of BK nephropathy are predictors of graft loss …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study of the histologic evolution of BK nephropathy has recently shown the link between BK nephropathy and antibody‐mediated rejection, but in both studies were limited by their lack of standardized de novo DSA screening . Previous work has shown that features of antibody‐mediated rejection (glomerulitis and peritubular capillaritis) in the setting of BK nephropathy are predictors of graft loss …”
Section: Discussionmentioning
confidence: 99%
“…27,28 Previous work has shown that features of antibody-mediated rejection (glomerulitis and peritubular capillaritis) in the setting of BK nephropathy are predictors of graft loss. 29 The association between medication nonadherence and dnDSA has been well-documented, 15,18,19,[30][31][32] but few studies have systematically examined the relationship between physician directed immunosuppression reduction for infectious disease reasons and subsequent development of dnDSA. 33 immunosuppression reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for laboratory monitoring of BK viremia and adjustment of immunosuppression at our center was performed as previously described. 3,12 Briefly, plasma BK PCR was monitored every 2 weeks for the first 3 months post-transplant, then monthly until 6 months post-transplant, and then every 3 months until 18 months post-transplant. Allograft biopsy was performed if BK PCR was positive and/or creatinine was elevated 25% above baseline.…”
Section: Protocol For Bk Laboratory Monitoring and Immunosuppressiomentioning
confidence: 99%
“…Risk factors for BK virus reactivation are incompletely understood, though a myriad of risk factors have been posited including characteristics pertaining to the graft, recipient, and type of immunosuppression regimen. Graft‐related risk factors include ischemic allograft injury, prior acute rejection, degree of HLA mismatch, high BK‐specific antibody titers, and BK serologic mismatch (seropositive donor and seronegative recipient), though serologic status is not routinely clinically assessed . Recipient‐related risk factors for BK reactivation include older age, Caucasian ethnicity, and male sex .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation